PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN - Muhtar S. Hidayat (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2012)
Abstract : Contextual Learning (Contextual Teaching and Learning), which is influenced by the philosophy of constructivism, is a learning concept that links between the material taught to students’ realworld situations, and encourages students to make connections between the knowledge he has with the application in their daily lives. In the context in which the application pembeljaran involving seven major components, namely: constructivism, questioning, inquiri, learning community, modeling, and authentic assessment. Keywords: Learning, Contextual.